Annatto carotenoids attenuate oxidative stress and inflammatory response after high-calorie meal in healthy subjects. (October 2017) - Roehrs, Miguel; Conte, Lisiane; da Silva, Dariane Trivisiol; Duarte, Thiago; Maurer, Luana Haselein; de Carvalho, José Antonio Mainardi; Moresco, Rafael Noal; Somacal, Sabrina; Emanuelli, Tatiana
Abstract: The aim of this study was to evaluate the effect of annatto carotenoids intake associated to a single high-calorie meal (high fat and high carbohydrate) in postprandial biochemical, inflammatory and oxidative stress markers. Twelve healthy subjects (6 men, 6 women) were included in this randomised, controlled crossover study. Baseline blood samples were collected from fasting subjects that immediately received high-calorie meal without carotenoid (placebo) or containing 1.2 mg/kg bixin (BIX) or 0.06 mg/kg norbixin (NBIX). Blood samples were taken 60, 120 and 240 min after meal intake. NBIX intake did not affect biochemical blood markers but reduced the postprandial levels of inflammatory cytokines (IL-1, IL-6 and TNF-α) and lipid oxidation 60–120 min after meal. BIX only partially prevented postprandial-induced lipid oxidation. Results indicate that the intake of NBIX may be an alternative to reduce the postprandial inflammatory and oxidative stress responses to high-calorie meals. Graphical abstract: Highlights: Effects of annatto carotenoids associated to high-calorie meal in human subjects Bixin and norbixin did not change postprandial blood glucose, insulin or lipid levels. Norbixin reduced postprandial LDL and lipid oxidation and inflammatory cytokines. Norbixin increased postprandial activity of blood glutathione peroxidase. Bixin only partially prevented postprandial lipid oxidation.